Capital structure choice: a case study on New Zealand's unlisted firms. (29th April 2014) - Wellalage, Nirosha Hewa; Locke, Stuart
This paper investigates the determinants of capital structure in unlisted firms in New Zealand. Hypotheses utilising pecking order theory, trade-off theory and agency costs theory and the effects of firm ownership structure, firm characteristics and industry on small business capital structure determinants are empirically examined. 11 years of data for 120 unlisted small businesses are collected and 1320 observations are analysed using dynamic panel GMM estimation. The results indicate that managerial ownership, firm characteristics and industry are important determinants of capital structure. Moreover, this study finds firm ownership and characteristics have opposing relationships with long- and short-term capital structure choices. Though the results generally support pecking order theory, they indicate a potential need for different capital structure theories for long-term debt choice and short-term debt choice, in small firms.